Factors Influencing Political Stability in South America: The Roles of Rule of Law, Regulatory Quality, Control of Corruption, and Government Effectiveness - Muhammad Ardiansyah; Achmad Nurmandi; Herman Lawelai; Muhammad Younus; Wahdania Suardi; Sandi Lubis (Greenation Research & Yayasan Global Resarch National, 2026)
Political stability in South America varies significantly across countries and is closely linked to differences in governance quality and institutional capacity. This study aims to analyze the relative influence of the rule of law, regulatory quality, control of corruption, and government effectiveness on political stability across 12 South American countries. The research employs an explanatory quantitative design using cross-national secondary data, analyzed through descriptive statistics, correlation analysis, and multiple linear regression. The findings indicate that all governance dimensions are positively associated with political stability; however, only the rule of law shows a statistically significant effect when all variables are analyzed simultaneously. Other dimensions lose significance, suggesting overlapping roles and potential institutional substitution. These results demonstrate a hierarchical relationship among governance dimensions. The study concludes that strengthening legal institutions and law enforcement is the most critical factor in sustaining long-term political stability in South America.